KAJIAN KEBIJAKAN IMPLEMENTASI PROGRAM KESEHATAN REPRODUKSI REMAJA UNTUK MENGHASILKAN MODEL PEMBERDAYAAN REMAJA - Pandawa, Rugaya Munawar; Djama, Nuzliati T (Media Penelitian dan Pengembangan Kesehatan, 2024)
It is hoped that the existence of a youth posyandu will become a forum for empowering teenagers, especially those who have limited access or geographical barriers such as remote areas, island areas, outermost or isolated areas. The aim of this research was to examine the policy of the Adolescent Reproductive Health (KRR) program implemented by the community health center and develop a policy model for adolescent empowerment. This policy study research is a qualitative study using interviews and FGDs to examine the implementation of the KRR program and the results can develop strategic policies. The researcher then conducted a Focus Group Discussion. Total of 16 posyandu from 8 community health centers in Morotai Island Regency were chosen as research locations. Data collection during August 2023. Only 4 community health centers have active posyandu (Daruba, Sangowo, Morodadi, and Tiley), 1 community health center (Wayabula) has joined Posbindu, 3 youth posyandu are integrated with the School Health Unit (UKS) program implemented in junior and senior high schools. Data analysis was carried out using theme analysis. Facilities and infrastructure have not been met according to standards and guidelines are incomplete at the youth posyandu. Most teenagers are less active in using youth Posyandu if it is implemented in villages compared to implementation in integrated schools with the UKS program. In conclusion, the achievement of the KRR program objectives has not been optimal. The development of a youth empowerment policy model is carried out based on the resulting policy brief.